2014
DOI: 10.1177/1078155214520821
|View full text |Cite
|
Sign up to set email alerts
|

Fixed, low-dose rasburicase for the treatment or prevention of hyperuricemia in adult oncology patients

Abstract: Fixed, low dose rasburicase produced a consistent lowering of uric acid levels and may be utilized in the management of hyperuricemia in TLS. Further study is necessary to determine if a larger fixed dose would be required in those patients with a higher baseline uric acid level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 11 publications
3
45
2
Order By: Relevance
“…[26][27][28] In our cohort, AKI developed in 25% children (n = 30/120) with TLS, of which five children required hemodialysis (4%). The requirement of dialysis in our study is similar to or less than that reported previously, [29][30][31][32] even without the prophylactic use of rasburicase in HRD and despite having a large proportion of patients presenting with AKI. We observed a 1.7% (n = 2) suspected TLS mortality in the study population.…”
Section: Discussionsupporting
confidence: 88%
“…[26][27][28] In our cohort, AKI developed in 25% children (n = 30/120) with TLS, of which five children required hemodialysis (4%). The requirement of dialysis in our study is similar to or less than that reported previously, [29][30][31][32] even without the prophylactic use of rasburicase in HRD and despite having a large proportion of patients presenting with AKI. We observed a 1.7% (n = 2) suspected TLS mortality in the study population.…”
Section: Discussionsupporting
confidence: 88%
“…Campara et al reported that a single low (0.15 mg/kg) dose of rasburicase based on optimal body weight was sufficient to lower urate levels and appeared as effective as the significantly higher doses for multiple days (10). Herrington et al had adjusted their hyperuricemia algorithm to determine the 3-or 6-mg low-dose rasburicase on the baseline UA level (11). Owing to the relatively high cost associated with its use, rasburicase is typically administered at low doses and for <5 days in patients with malignancies attributed to lead exposure to minimize the cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The labeled dose is 0.2 mg/kg, daily given as a 30-min IV infusion, for up to 5 days [72]; however, in patients with low-intermediate risk of TLS, the smaller doses (0.1-0.15 mg/kg) were demonstrated to be also efficient, allowing for substantial cost reduction [81]. Alternatively, for patients with the low to moderate risk, a single fixed (3, 4.5, 6, or 7.5 mg) or weightbased (0.15-0.20 mg/kg) dose regimen has been proposed, and its efficacy is demonstrated [82][83][84][85][86][87][88]. A systematic review and meta-analysis of 19 studies by Yu et al [89] revealed that single doses of rasburicase: 6 mg for adults and 1.5 and 0.15 mg/kg for children, were sufficient to normalize and sustain lower uric acid and creatinine levels in adults with TLS.…”
Section: Rasburicasementioning
confidence: 99%